Extruded meat analogues based on yellow, heterotrophically cultivated Auxenochlorella protothecoides microalgae. (January 2020) - Caporgno, Martín P.; Böcker, Lukas; Müssner, Christina; Stirnemann, Eric; Haberkorn, Iris; Adelmann, Horst; Handschin, Stephan; Windhab, Erich J.; Mathys, Alexander
Abstract: Alternatives to animal proteins with similar texture, appearance and taste are demanded by an increasing group of consumers. Plant-based meat analogues produced by high moisture extrusion cooking can provide relevant solutions. Here, microalgae combined to soy concentrates were shown to create fibrillary textured extrudates. The incorporation of spray-dried microalgae biomass in up to 50% affected the formation of fibers, which could be balanced by reducing moisture levels. The elevated fat content of microalgae biomass led to lubrication effects, while probably undisrupted microalgae cells acted as passive fillers and limited the access of intracellular proteins. Both effects may have reduced texturing but increased tenderness in comparison to pure soy based extrudates. By using heterotrophically cultivated Auxenochlorella protothecoides with a light-yellow coloration, a consumer-adverse visual appearance could be omitted. Microalgae integration improved the extrudate's nutritional profile by incorporating vitamins B and E, where over 95% was retained in the final product. Industrial relevance: The meat analogue industry strives to be more than an alternative for vegetarian and vegan customers. Large initial public offerings of relevant players underline the current economic and industrial interest. Besides animal wellbeing, meat analogues are praised mainly for their reduced ecological and environmental impact. Yet, most of the products on the market are based on environmentally questionable resources, such as soy. Hence, this study with focus on microalgae as a protein alternative to the ubiquitously applied soy protein concentrate is relevant to the evolving industry and research. In this manuscript, a fibrillary textured plant-based product using microalgae is shown without an adverse color. Graphical abstract: Unlabelled Image Highlights: Bright yellow fibrillary meat analogues were produced using heterotrophic microalgae. Moisture reduction was required to develop fibers with increasing microalgae content. Microalgae cells remained visible after the extrusion processing. Enhanced nutritional value of extrudates as a result of microalgae incorporation.